Necessidades educacionais básicas da alfabetização em Braille - Vianna, Clecimara (2021)
Linked to the Professional Master's in Public Policy and Educational Management, in the line of research related to Pedagogical Management and Educational Contexts, this paper presents a study on visual impairment and literacy. The general objective of this research is to know the basic educational needs that involve the learning process in reading and writing in Braille. The method used was field research with a qualitative approach. A text was composed based on the analyzed data, using content analysis. The data collection instrument was a questionnaire, addressed to two teachers from the Specialized Educational Service (SEE), five teachers from regular classrooms and two Braille literacy teachers. It was found that the teachers were interested in participating in training on the themes of literacy and visual impairment, as there are still many doubts regarding this subject. It was verified the presence of uncertainties and anxieties for literacy in Braille. Learning how to teach from a continuing education perspective and in the area of visual impairment is required, in view of the specificities of the Braille literacy process. It was concluded that the study pointed out the need for pedagogical and administrative strategies, so that the student with visual impairment (blindness) can enjoy the rights that the legislation advocates in the educational scope. As a final product, an identification matrix was developed to identify the conditions necessary for literacy in Braille.